Technology Adaptation Patterns and Third-Level Digital Divide: Analyzing Workplace Communication at PT. Pesta Pora Abadi - Nurul Fatihah; Reza Safitri; Yuyun Agus Riani (FAKULTAS DAKWAH UIN SALATIGA, 2026)
This study provides an exploratory overview of patterns of technological adaptation as a fundamental factor contributing to the intergenerational digital divide between Generation Z and Millennials at PT Pesta Pora Abadi. Unlike previous literature, which often emphasizes access to infrastructure or basic technical skills, this study argues that the root of the digital divide lies in differences in how individuals internalize and operationalize new technologies in the workplace. Using a descriptive qualitative design, data were collected through in-depth interviews and Focus Group Discussions (FGDs). Thematic analysis identified five distinct adaptation patterns: intuitive-agile adaptation, structured-procedural adaptation, learning speed disparities, resistance to specific platforms, and the contradiction between integrity-based validation and efficiency. The findings reveal that these differing patterns create systemic noise in corporate communication, regardless of the individual’s level of technical proficiency. Practically, this study recommends that organizations implement reverse mentoring and align the digital growth mindset with corporate values (I-ACT) to bridge this gap.